Education on Innovation of Processed Beverages Made from Turmeric and Telang Flowers as Tourism Kampong Products - Titisari, Ema Yunita; Asikin, Damayanti; Herlindah; Dewi, Heptari Elita (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
People in Baran Buring Village, Malang City produce turmeric. There are still many of them living below the poverty line. To improve the community's economy, the Tourism Kampong program was initiated and driven by the Tholabie Islamic Boarding School in collaboration with academics. This Public Service (PKM) program aims to educate people how to process turmeric and telang flower into popular beverages. The method used is educating and training people about how to produce popular beverages made from turmeric and telang flower. The results achieved are: the increasing of people knowledge about the benefits of telang and turmeric flowers (80%) and the skill in produce turmeric and telang flowers (90%). This beverage product can be a souvenir as well as a reinforcement of the character of Kampoeng Eduwisata Buah Bercahaya.